Analysis of Prospective Science Teachers’ Practicum Competencies in Promoting Sustainable and Quality Education (SDG 4) - Mohammad Liwa Ilhamdi; Agil Al Idrus; Aliefman Hakim; Lalu Zulkifli; Aris Doyan; AA Sukarso (Jurnal Penelitian Pendidikan IPA, 2026)
Field practicum skills are a cornerstone of the professional competence of prospective biology teachers, yet their long-term developmental dynamics remain underexplored. This study aims to map the profile of field practicum abilities among Biology Education students at the Mataram University over a five-year period (2020-2024). Using a longitudinal quantitative approach, data were collected from 120 students through a structured, expert-validated questionnaire and analyzed using descriptive statistics and the non-parametric Kruskal-Wallis and Dunn's tests. The results indicate significant fluctuations in competency achievement: the highest average was in 2022 (79.28; SD=3.13) and the lowest in 2023 (65.93; SD=0.78). The Kruskal-Wallis test confirmed significant differences between years (χ² = 80.67; p < 0.05), with specific year pairs (e.g., 2022 vs. 2023) showing marked disparities. These findings reveal that field practicum ability is highly susceptible to curricular factors, institutional policies, and external disruptions such as extreme weather. The implication is that the development of prospective science teachers requires a learning ecosystem that is adaptive, evidence-based, and capable of proactively responding to environmental uncertainty.